Recalibrating Institutional Choreographies for a Future Focused Education - Som Naidu (Commonwealth of Learning, 2019)
Contemporary educational institutions are experiencing disruptions to their modus operandi from a variety of sources. A changing student demographic across the higher education sector, along with their changing educational needs is driving much of this disruption. Other drivers are the need for different kinds of skill sets required in the contemporary workplace, the need for alternative methods of credentialing and a demand for flexibility in the education space. However, if you looked around for how prepared our contemporary educational institutions are for leading learning for the future, you are likely to be disappointed. This is not because our current educational system is broken en masse. In fact, there are plenty of examples of excellent practices all around us, but these are not enough. Our universities and educational systems continue to operate on outdated principles and practices. While they are willing to experiment with new models on the peripheries of their core business, most are not bold enough to rethink and reconfigure their mainstream processes. It is rare to find large-scale and enterprise-wide operations that are appropriately aligned to lead learning and teaching for the near and the long-term future. Why is this so? What can, and must be done about it? This paper examines potential areas of disruption, their key drivers, and where and how to begin a rethink and recalibration of how universities can create, capture and deliver value.